Is Substantial Lymphovascular Space Invasion Prognostic for Clinical Outcomes in Type II Endometrial Cancer?. Issue 7 (July 2022) - Jaishankar, S.; Pifer, P.M.; Bhargava, R.; Keller, A.; Musunuru, H.B.; Patel, A.K.; Sukumvanich, P.; Boisen, M.; Berger, J.L.; Taylor, S.; Courtney-Brooks, M.; Olawaiye, A.; et al.
Abstract: Aims: Substantial lymphovascular space invasion (LVSI) compared with none or focal LVSI is predictive of lymph node involvement and worse clinical outcomes in endometrioid-type endometrial carcinoma. We aimed to quantify the incidence of substantial LVSI in type II (clear cell and serous) endometrial cancer and correlate the extent of LVSI with clinical outcomes. Materials and methods: A retrospective review was conducted on type II endometrial cancer patients who underwent surgical management from July 2017 to December 2019 using the three-tier LVSI scoring system. Binary logistic regression and Cox regression were used to analyse predictors of lymph node involvement or survival outcomes, respectively. The Kaplan–Meier method and Log-rank test were used to analyse differences in locoregional disease-free survival (LR-DFS), distant metastasis disease-free survival (DM-DFS) and overall survival between patients with substantial versus none/focal LVSI. Results: In 79 patients with type II endometrial carcinoma, no LVSI, focal LVSI and substantial LVSI was present in 48.1%, 15.2% and 36.7% of patients, respectively. Lymph nodes were involved in 0.0% with no LVSI, 20.0% with focal LVSI and 60.0% with substantial LVSI ( P < 0.001). The median follow-up was 22.2 months. In patients with none/focal versus substantial LVSI, the 2-year LR-DFS and DM-DFS rates were 91.5% versus 71.4% ( P = 0.01) and 90.2% versus 63.8% ( P = 0.005), respectively. On univariate analysis, myometrial invasion ≥50%, tumour size ≥3.6 cm, substantial versus none/focal LVSI, lymph node involvement and omission of adjuvant radiotherapy were significant predictors for worse LR-DFS and DM-DFS ( P < 0.05). Discussion: Substantial LVSI has a high incidence in type II pathology at our institution and predicts for lymph node involvement and worse clinical outcomes. Highlights: Substantial LVSI was present in 36.7% of patients with type II endometrial cancer. Lymph nodes were involved 60.0% of patients with substantial LVSI. At 2 years of follow-up, substantial versus none/focal LVSI predicted for worse LR-DFS and DM-DFS.